AB0188 Combination therapy with adalimumab plus methotrexate reduces circulating levels of pro-matrix matalloproteinases-1 and -3 independently of clinical disease activity in patients with rheumatoid arthritis. (23rd January 2014) - Mozaffarian, N.; Karunaratne, M.; Kupper, H.
Abstract : Background: In patients (pts) with rheumatoid arthritis (RA), therapy with biologic agents such as adalimumab (ADA) can uncouple destruction of articular cartilage and bone from the inflammatory processes that drive clinical disease activity. Although mechanistic insights into this uncoupling are lacking, elevated levels of matrix metalloproteinases (MMPs), driven by cytokines (eg, TNFa), have been associated with the erosive loss of cartilage and bone. Objectives: To evaluate the impact of ADA+methotrexate (MTX) vs placebo (PBO)+MTX on pro-MMP-1 and pro-MMP-3 serum levels in the context of RA disease activity after 24 weeks. Methods: ARMADA was a 24-week, phase 2/3, PBO-controlled, dose-ranging trial of ADA in pts with established RA and an inadequate response to standard DMARD therapy. Pts received MTX co-therapy. Serum samples and disease activity measures were collected at baseline and weeks 4, 12, and 24. Mean change from baseline in pro-MMP-1 and -3 were summarized for pts based on 2 measures of disease status at final visit [low disease activity (LDA), defined as DAS28(CRP) <3.2; clinically meaningful improvement (CMI), defined as decrease in DAS28(CRP) >1.2]. Last observation carried forward was used to impute missing data in this post hoc analysis. Results: Data were available from 209 pts treated with ADA+MTX and 62 pts treated with PBO+MTX. At final visit, 43% (n=89) and 71% (n=149) of ADA+MTX-treated pts achieved LDA and CMI, respectively, vs 8% (n=5) and 21% (n=13) of PBO+MTX-treated pts. In the ADA+MTX group, baseline levels of pro-MMP-1 and -3 were similar regardless of LDA or CMI attainment (Table ). However, in the PBO+MTX group, baseline levels of pro-MMP-1 and -3 were substantially lower in pts who achieved LDA, but not CMI, vs non-responders. Substantial reductions in pro-MMP-1 and -3 were apparent in all ADA+MTX groups over time, although pts who achieved CMI had greater decreases in pro-MMP-1 and -3 than those who did not, and declines were more rapid in pts who achieved LDA than those who did not. Interestingly, in pts treated with PBO+MTX, circulating levels of pro-MMP-1 and -3 did not decrease over time, irrespective of final disease status. Conclusions: These data provide insights into the mechanism(s) by which ADA+MTX protects against radiographic joint damage despite ongoing clinical symptoms. ADA+MTX therapy in pts with established RA led to rapid declines in the circulating levels of pro-MMP-1 and -3, irrespective of impact on clinical disease activity. In contrast, pro-MMP levels were not reduced in PBO+MTX-treated pts. Baseline pro-MMP levels were substantially lower in PBO+MTX-treated pts who achieved LDA than those who did not, underscoring the potential capacity of circulating pro-MMP levels for predicting response to MTX monotherapy. Acknowledgements: AbbVie Inc. sponsored the study, contributed to its design, and participated in the analysis and interpretation of the data, and in the writing, reviewing, and approval of the final version of the abstract. Medical writing support was provided by Benjamin Wolfe, PhD, of AbbVie Inc. Disclosure of Interest: N. Mozaffarian Shareholder of: AbbVie Inc., Employee of: AbbVie Inc., M. Karunaratne Shareholder of: AbbVie Inc., Employee of: AbbVie Inc., H. Kupper Shareholder of: AbbVie Inc., Employee of: AbbVie Inc.